1997
DOI: 10.1128/mcb.17.8.4434
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of T-Cell Antigen Receptor Signalling by Syk Tyrosine Protein Kinase

Abstract: T-cell antigen receptor (TCR) signalling has been shown to involve two classes of tyrosine protein kinases: the Src-related kinases p56lck and p59 Stimulation of T cells by antigen or anti-T-cell receptor (TCR)antibodies results in the rapid tyrosine phosphorylation of several intracellular proteins (for reviews, see references 26, 38, and 40). This signal predicates all subsequent biochemical and biological events of T-cell activation. Since the TCR and the associated CD3 and zeta () chains are devoid of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 43 publications
(59 reference statements)
3
78
1
Order By: Relevance
“…Syk is associated with the T-cell receptor prior to the stimulation, and CD3 engagement induces activation of Syk, independent of Lck or CD45 (32,33). In addition, Syk augments tyrosine phosphorylation of CD3 to stimulate the kinase activity of Syk by itself (34). We have demonstrated that 3BP2 is preferentially tyrosine-phosphorylated by Syk in COS-7 cells.…”
Section: Phosphorylation Of Tyr 446 But Not the Sh2 Domain Of 3bp2 Comentioning
confidence: 76%
“…Syk is associated with the T-cell receptor prior to the stimulation, and CD3 engagement induces activation of Syk, independent of Lck or CD45 (32,33). In addition, Syk augments tyrosine phosphorylation of CD3 to stimulate the kinase activity of Syk by itself (34). We have demonstrated that 3BP2 is preferentially tyrosine-phosphorylated by Syk in COS-7 cells.…”
Section: Phosphorylation Of Tyr 446 But Not the Sh2 Domain Of 3bp2 Comentioning
confidence: 76%
“…In the standard model of TCR signaling, phosphorylation of ITAM on the CD3 subunits by Src family kinases is a prerequisite for Syk family kinases to bind and become activated. While this appears to be true for Zap70, Syk can be activated by TCR signaling even in the absence of Src family kinase activation, probably because, unlike Zap70, it can phosphorylate the ITAM directly [35][36][37]. Despite this, Zap70 has been reported to be much better than Syk at promoting phosphorylation of the TCRf chain by recruiting Lck to the signaling complex [38].…”
Section: Discussionmentioning
confidence: 99%
“…Full protection of these riboprobes by cellular luciferase transcripts resulted in a 282-nucleotide fragment. Size markers were prepared by end-labeling MspI-digested pBR322 fragments with Klenow DNA polymerase and [␣- Transfections-BI-141 cells were stably transfected by electroporation (260 V, 960 microfarads) and selected in the presence of G418 (0.75 mg/ml), according to a protocol described elsewhere (36). Monoclonal cell lines expressing the transfected cDNAs were identified by a combination of RNase protection assays and immunoprecipitations (data not shown).…”
Section: Methodsmentioning
confidence: 99%